2022
DOI: 10.1002/aepp.13332
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in food insecurity among Black and White households: An analysis by age cohort, poverty, education, and home ownership

Abstract: We use the Current Population Survey's Food Security Supplement data to investigate food insecurity disparities among Black and White households across different age groups and socioeconomic characteristics. We find that disparities in the probability of food insecurity between Black and White households vary considerably across specific socioeconomic strata, in particular education, poverty status, and home ownership. Black households are systematically more food insecure than White, even when conditioning on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our results are consistent with research from other high-income countries, which have found that disabled people generally have higher risk of FI than non-disabled people as a result of disadvantage ( 13 , 31 ) . Previous research has also suggested that FI decreases with age ( 31 , 32 ) , but that some groups of older people such disabled people and who are disadvantaged may still be at higher risk of FI at older ages ( 7 , 21 ) . Our findings also support research that indicates that wealth and assets such as savings are particularly important for disabled peoples’ food security ( 33 ) ; indeed, savings eliminated the difference in FI risk between disabled and non-disabled people in older age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with research from other high-income countries, which have found that disabled people generally have higher risk of FI than non-disabled people as a result of disadvantage ( 13 , 31 ) . Previous research has also suggested that FI decreases with age ( 31 , 32 ) , but that some groups of older people such disabled people and who are disadvantaged may still be at higher risk of FI at older ages ( 7 , 21 ) . Our findings also support research that indicates that wealth and assets such as savings are particularly important for disabled peoples’ food security ( 33 ) ; indeed, savings eliminated the difference in FI risk between disabled and non-disabled people in older age.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have been identified as having systematically higher risk of FI. These include people in receipt of income-replacement social security, people who are unemployed or underemployed, adults in younger age groups and people from disadvantaged groups (1,(7)(8)(9) . Similarly, disabled people have also been found to be at higher risk compared with non-disabled people across several high-income countries (1,(10)(11)(12)(13)(14) .…”
mentioning
confidence: 99%
“…We, agricultural and applied economists, have tended not to direct our models and analysis to get at these mechanisms of disparities observed in food insecurity. However, Joshua Berning, Alessandro Bonanno, and Rebecca Cleary (2022, p. 3) argued “unobserved factors may be contributing to the racial disparity in [food insecurity].”…”
Section: Food Security Todaymentioning
confidence: 99%
“…Does our literature have a broader view of race and ethnicity? Do the work of McCluskey (2022) and Berning et al (2022) reflect a long‐standing tradition, or do they reflect a potential shift in the discipline's approach to racial injustices in the food system? To address these questions, my colleagues and I collected 86 presidential addresses and 3915 invited papers published between 1919 and 2022, 4001 papers in total, for a content analysis.…”
Section: Content Analysismentioning
confidence: 99%
“…In particular, Black‐ and Hispanic‐headed households perennially have higher food insecurity rates than White‐headed households, as shown in Figure 1, and food insecurity is likely a contributing factor to the disadvantaged status of these groups. Yet, few studies have analyzed the differential exposure to food insecurity across racial and ethnic groups (the exceptions include Berning et al, forthcoming; Flores‐Lagunes et al, 2018; Gundersen, 2008; and Nam et al, 2015).…”
Section: Inequality In Food Insecurity and Snapmentioning
confidence: 99%